Etnomatematika Permainan Tradisional Congklak Sebagai Penerapan Konsep Matematika - Windi Astuti; Sri Tirto Madawistama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Ethnomathematics plays an important role in improving mathematics learning because it connects mathematical concepts with students' experiences in everyday life related to local arts and culture. This helps students better understand the concepts being taught. This research aims to explore the mathematical concepts contained in the traditional game congklak. This research uses the literature study method. The data that has been obtained is then analyzed using descriptive analysis methods. Based on an analysis of the history and philosophy of the congklak game, it was found that this game includes various mathematical concepts, such as plane shapes (half circle, circle, rectangle) and space shapes (half ball), the concept of transformation in the form of reflection/mirror and number patterns. Apart from that, the congklak game involves number operations such as addition, subtraction, multiplication and division, and has cultural and philosophical values.